The Type of Hierarchical Leadership in Strated And Sustained Management in organization - Dadah Muliansyah (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
Leadership is the way a leader behaves, communicates, and interacts with members of his subordinates, the process of influencing people to conduct their direction, the influence of leadership can vary depending on motivation or orientation towards a particular task. Some leadership styles include positive leaders and negative leaders, where the differences are based on the way and effort they motivate their subordinate members, if the approach in motivation is emphasized on both economic and non-economic rewards, which means using a positive leadership style. So if his approach emphasizes sanction or punishment, then he implements a negative leadership style. This second approach can result in acceptable achievements in many situations, but leads to loss of insensitivity to members of their subordinates